Current status of short video as a source of information on lung cancer: a cross-sectional content analysis study - Zhao, Xinyu; Yao, Xinyi; Sui, Binbin; Zhou, Yutao (Frontiers in Oncology, 2024)
BackgroundThe morbidity and mortality rates of lung cancer continue to rise, leading to a significant disease burden. Health education on lung cancer serves as an effective approach for prevention and treatment. With the increasing popularity of the Internet, an escalating number of patients are turning to video platforms for health information. Short videos facilitate better absorption and retention of information, thus becoming the primary channel for health education communication. However, the quality of information provided in videos on these platforms remains uncertain. Therefore, this study aims to assess the information quality pertaining to lung cancer in short videos available on a Chinese video platform.MethodsLung cancer-related videos on two short video platforms (TikTok and Kwai) were screened, and only Chinese (Mandarin) videos were included. The Global Quality Score (GQS) and modified DISCERN (mDISCERN) tools were then used to evaluate the quality and reliability of the information. A comparative analysis was conducted on videos from various sources. Additionally, correlation analysis was employed to investigate the factors influencing video quality.ResultsAfter screening, a total of 186 videos were included. The median GQS score and mDISCERN score were 3 (IQR: 3-4) and 2 (IQR: 2-4), respectively. A total of 44.1% of the lung cancer videos provided a comprehensive explanation of the symptoms, while only 3.2% fully explanation the complications associated with lung cancer. Health professionals, particularly specialists, demonstrated higher quality video information compared to individual users (P<0.001). The correlation coefficient between GQS score and mDISCERN score was 0.340, showing a significant positive correlation (P<0.001). In addition, GQS score was positively correlated with video duration (r=0.177, P=0.015)ConclusionThe information quality of the 186 videos screened by the two platforms in this study was generally unsatisfactory. However, videos provided by experts were deemed relatively reliable, with video duration being closely associated with information quality. Therefore, it is crucial to meticulously screen high-quality and dependable videos on the platform in order to effectively guide lung cancer prevention and treatment.